Kesulitan Belajar Mahasiswa Pendidikan Matematika - Anisa Risanda Damanik; Rusi Ulfah Hasanah; Dahlianasari Syahputri; Riana Riana (International Forum of Researchers and Lecturers, 2024)
Learning difficulties do not only occur in students attending primary to secondary school, but also occur in mathematics education students. This research uses the Systematic Literature Review research method. Mathematics education students are part of the teaching faculty who are hired to become educators, namely the inability to understand the material, this main factor is the main factor in the difficulty of learning mathematics, students in the first semester are vulnerable to semesters 1-3 where the learning method is between schools. and different lectures make students in the first semester of mathematics education experience a shock of understanding, students are required not only to gain understanding in lecture classes but also in seminars, presentations and research, this study concludes. But one of the main factors is external where jockeying has a domino effect Mathematics education students must be aware of this so that they do not become students who are dull in thinking, logic and the future. The author states that no matter how smart the student is, if they still use assignment coaching services, they can be said to be suffering from an illness as is another definition of learning difficulties..